Targeting interleukin-1 signaling for renoprotection - Bogdanova, Daria; Samsonov, Mikhail Y.; Lebedeva, Svetlana; Bukhanova, Darya; Materenchuk, Maria; Mutig, Kerim (Frontiers in Immunology, 2025)
Sterile inflammation with ensuing immune-mediated kidney damage has been implicated in pathophysiology of acute and chronic kidney diseases. Disinhibition of interleukin 1 (IL-1) signaling triggers local inflammation of renal tissue and may initiate or aggravate systemic inflammatory response. The IL-1α isoform is released by many cell types during cell necrosis to attract immune cells, whereas the IL-1β isoform is secreted by immune cells to amplify local inflammatory responses. The unfolding of IL-1 signaling is restricted by an endogenous IL-1 receptor antagonist and a decoy IL-1 receptor variant. Pharmacological IL-1 inhibitors mimicking the natural IL-1 suppressors are instrumental in management of a broad spectrum of (auto)inflammatory disorders. Progression of several kidney diseases toward renal fibrosis has been associated with a disbalance between the pro-inflammatory and anti-inflammatory IL-1 signaling components. While IL-1 inhibitors have proven success in prevention and treatment of renal complications accompanying the autoimmune disorders, broader opportunities in kidney diseases have been expected. The present review work analyzes potential niches for IL-1 signaling in the field of nephrology.